Inhibition of bacteria contaminating alcoholic fermentations by killer yeasts - Meneghin,Maria Cristina (2010)
The aim of this work was to study the in vitro antibacterial activity possessed by killer yeast strains against bacteria contaminating alcoholic fermentation (Bacillus subtilis, Lactobacillus plantarum, Lactobacillus fermentum and Leuconostoc mesenteroides), in cell X cell and cell X crude toxin preparations. The bacteria were not inhibited by any S. cerevisiae killer strains (5 out of 11). The inhibition caused by two crude toxin preparations (Trichosporon figueirae and Candida sp) against L. plantarum was surprisingly high but not in the same extent for B. subtilis, especially with three killer strains (Candida glabrata, Pichia anomala and Candida sp). L. mesenteroides and L. fermentum strains were neither inhibited in cell X cell nor crude toxin X cell tests. The results suggested that killer activity of yeasts might operate over bacteria and it could be used for the biocontrol of contaminating bacteria from alcoholic fermentation if additional tests on toxin application in fermentation shown to be successful. A wider panel of S. cerevisiae killer strains should be used to confirm that they were really unable to control the growth of these Gram-positive bacteria.